A criminological exploration of patrons’ interaction with bouncers - Mbhele, Nkosingiphile (Acta criminologica, 2019)
Nightclubs in South Africa rely heavily on private security personnel to protect their property and ensure the safety of patrons during busy nights. However, the use of physical force by private security guards, which is often coupled with thuggery and unprofessional behaviour, is a concern among many interest groups and scholars. Bouncers should be employed in a professional capacity as their functions are regulated by the Private Security Industry Regulatory Authority (PSIRA) that adopted a Code of Conduct, which should be adhered to by all private security concerns and their employees. The focus of the study was to investigate the nature of the interaction between bouncers and patrons. It is postulated that trained and qualified private security personnel are better skilled and equipped to respond to risky and dangerous circumstances than untrained and unqualified private security personnel. It was in this direction that the researchers engaged in an investigation of private security compliance with PSIRA and their obligation and interaction with patrons. Nine male bouncers and one female bouncer as well as twenty undergraduate students from the University of KwaZulu-Natal were sampled. It was found that, although the bouncers had experienced physical altercations with patrons, their relationships with some male, and particularly with most female patrons, was positive. However, most of the bouncers had never received appropriate training and neither were they registered with PSIRA.